A revolução dentro da ordem: uma interpretação da sociologia de Luiz Pereira (1933-1985) - Ludwig, Carlos Alexandre Will [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Investigate the trajectory and scientific production of the educator and sociologist Luiz Pereira (1933-1985) during the years 1955-1965 is the objective of this dissertation. Degree in Education from the College of Letters and Science Philosophy (FFCL), University of São Paulo (USP), Luiz Pereira worked as a teacher at various levels of education. As a researcher, participated since the late 50ies of the Brazilian intellectual debate on education and social development. This research point how the author's work was constituted through the perspective of understanding the social changes faced by Brazilian society - dilemmas and crises, in a context of intensified industrialization and urbanization process - realizing its limits, contradictions and singularities of this process. As guiding coordinates of the study, we used the concepts of history, biography and society according to what C. W. Mills developed in The sociological imagination

Investigar a trajetória e a produção científica do educador e sociólogo Luiz Pereira (1933-1985) durante os anos de 1955-1965 é o objetivo desta dissertação. Formado em Pedagogia pela Faculdade de Filosofia Ciências e Letras (FFCL) da Universidade de São Paulo (USP), Luiz Pereira atuou como docente nos diversos níveis do ensino. Enquanto pesquisador participou desde o final dos anos de 1950 do debate intelectual brasileiro sobre educação e desenvolvimento social. Pretendemos demonstrar que a obra do autor constituiu-se através da perspectiva de compreender as mudanças sociais enfrentadas pela sociedade brasileira - seus dilemas e crises, num contexto de intensificação do processo de industrialização e urbanização -, percebendo os limites, as contradições e singularidades deste processo. Como coordenadas orientadoras do estudo utilizamos os conceitos de história, biografia e sociedade de acordo com o desenvolvido por C. W. Mills em A imaginação sociológica
Keywords: Pereira, Luiz 1933; Sociologia; Mudança social; Capitalismo; Ciência política; Educação; Education